INFLUENCE OF pH ENVIRONMENT ON THE SPECTRAL AND OPTICAL PROPERTIES OF BETALAIN DERIVATIVES - Tuksanova Zilola Izatulloyevna; Nazarov Erkin Sadikovich; Toyirova Nodira Faxriddin qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article is devoted to the study of the influence of intermolecular interaction on the spectral and optical properties of food dyes. These studies make it possible not only to monitor the change in the color of dyes depending on the pH of the environment, temperature and other environmental factors, but also the use of food dyes in various branches of science and technology.